Animal Oppression and Human Violence: Domesecration, Capitalism, and Global Conflict - David A. Nibert (Columbia University Press, 2013)
Such long-held views about the role of other animals in human civilization have been widely accepted as obvious and unassailable. However, as Michael Parenti observes, â€œthe most insidious oppressions are those that so insinuate themselves into the fabric of our lives and into the recesses of our minds that we donâ€™t even realize they are acting upon us.â€ 3 This book offers a different point of view, one much neglected by academia. The thesis of this book is that the practice of capturing and oppressing cows, sheep, pigs, horses, goats, and similar large, sociable animals for human use did not, as Shaler put it, â€œset men well upon their upward way.â€ Rather, it undermined the development of a just and peaceful world. The harms that humans have done to other animalsâ€” especially that harm generated by pastoralist and ranching practices that have culminated in contemporary factory-farming practices â€”have been a precondition for and have engendered large-scale violence against and injury to devalued humans, particularly indigenous people around the world. Over the past ten thousand years, human lives and those of other animals have been shaped indelibly and tragically by the priorities and interests of elite groups in their societies. Those customs and practices that serve their interests include the much-touted process of â€œdomesticationâ€ of other animals, from which human civilization and advancement allegedly sprang. Cultural representations and even much scholarly discussion long have mainly supported and preserved societal practices that serve the interests of the most powerfulâ€”and the practice of exploiting other animals is no exception.